Alkaline Phosphatases Account for Low Plasma Levels of Inorganic Pyrophosphate in Chronic Kidney Disease - Laurain, Audrey; Rubera, Isabelle; Duranton, Christophe; Rutsch, Frank; Nitschke, Yvonne; Ray, Elodie; Vido, Sandor; Sicard, Antoine; Lefthériotis, Georges; Favre, Guillaume (Frontiers in Cell and Developmental Biology, 2020)
Introduction Patients on dialysis and kidney transplant recipients (KTR) present the syndrome of mineral and bone disorders (MBD), which share common traits with monogenic calcifying diseases related to disturbances of the purinergic system. Low plasma levels of inorganic pyrophosphate (PPi) and ectopic vascular calcifications belong to these two conditions. This suggests that the purinergic system may be altered in chronic kidney disease with MBD. Therefore, we perform a transversal pilot study in order to compare the determinants of PPi homeostasis and the plasma levels of PPi in patients on dialysis, in KTR and in healthy people. Patients and methods We included 10 controls, 10 patients on maintenance dialysis, 10 early KTR 3±1 months after transplantation and 9 late KTR 24±3 months after transplantation. We measured aortic calcifications, plasma and urine levels of PPi, the renal fractional excretion of PPi (FePPi), nucleoside triphosphate hydrolase (NPP) and ALP activities in plasma. Correlations and comparisons were assessed with non-parametric tests. Results Low PPi was found in patients on dialysis, (1.11[0.88-1.35], p=0.004), in early KTR (0.91[0.66-0.98], p=0.0003) and in late KTR (1.16 [1.07-1.45], p=0.02) compared to controls (1.66 [1.31-1.72] μmol/L). Arterial calcifications were higher in patients on dialysis than in controls (9 [1-75] versus 399 [25-526] calcium score/cm2, p < 0.05). ALP activity was augmented in patients on dialysis (113 [74-160], p=0.01) and in early KTR (120[84-142], p=0.002) compared to controls (64 [56-70] UI/L). The activity of NPP and FePPi were not different between groups. ALP activity was negatively correlated. Truncated at 250 words